Makanan dan Budaya Makan; Usaha Makanan Etnik “Warung Tegal” Pada Masyarakat Multikultur Jakarta - Juwono Tri Atmodjo; Susanne Dida (Jurnal Visi Komunikasi, 2020)
Jakarta as the capital city of Indonesia with a multicultural society causes a variety of types of food, eating procedures and ways of serving them as an illustration of the diversity of ethnicities, tribes and ethnic groups in Indonesia. Ethnic food, food from other nations, food products from the influence of popular culture, globalization, glocalization, and industrial products color the offering of dining options in Jakarta. Food as a cultural product is related to the way of life of the community not only to meet nutritional needs but also to the way of presentation and social cultural activities of the community. Ethnic food in multicultural communities in Jakarta is a typical ethnic food of an area which is used as a restaurant business community. Local wisdom on coastal and non-coastal food of the Javanese Tegal ethnic group as cultural capital for the gastronomic business of “Tegal Food Shop” in Jakarta.